Colombian birds collected by brother niceforo (1947)
Some time ago Brother Nicéforo, a well known naturalist of the Instituto de La Salle, Bogota, Colombia, very kindly presented a small collection of birds from his country to the United States National Museum. Although small in number of both specimens and species, it appears to have been a "picked" lot containing a surprising number of records of interest, some of which were undoubtedly puzzling to the collector. It is this material that is here reported on.  As may be noted in the body of this paper, not only is a form of tinamou, hitherto undescribed, made known to science, but the recorded geographic ranges of some thirteen other birds are hereby extended, including two additions to the recorded avifauna of Colombia.